2012
DOI: 10.1016/j.jcrs.2011.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Optical quality after myopic photorefractive keratectomy and laser in situ keratomileusis: Comparison using a double-pass system

Abstract: Retinal image quality was similarly reduced with PRK and LASIK, with no significant differences between the 2 methods. Some PRK patients had a residual refractive error that might have been related to corneal-wound healing still present 3 months postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 67 publications
1
37
0
2
Order By: Relevance
“…Cette plateforme permet l'analyse de toute atteinte de la transparence des milieux oculaires en quantifiant la diffusion de la lumière avec l'indice OSI. Elle a été ainsi utilisée pour l'étude de la qualité de vision après de la chirurgie réfractive par Lasik et Lasek par Lee et al [19], par PRK et Lasik par Ondategui et al [20], après la mise en place d'un ICL par Kamiya et al [21] ou pour quantifier la diffusion lumineuse lors d'uvéites par Nanavaty et al [22].…”
Section: Discussionunclassified
“…Cette plateforme permet l'analyse de toute atteinte de la transparence des milieux oculaires en quantifiant la diffusion de la lumière avec l'indice OSI. Elle a été ainsi utilisée pour l'étude de la qualité de vision après de la chirurgie réfractive par Lasik et Lasek par Lee et al [19], par PRK et Lasik par Ondategui et al [20], après la mise en place d'un ICL par Kamiya et al [21] ou pour quantifier la diffusion lumineuse lors d'uvéites par Nanavaty et al [22].…”
Section: Discussionunclassified
“…The double-pass Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 system has demonstrated good repeatability 12,14 and has already been used in optical quality evaluation after corneal refractive surgeries [16][17][18] and phakic intraocular lens implantation for myopia correction. 19,20 Preoperative optical quality is important as a reference value in evaluating the effects of refractive surgeries.…”
mentioning
confidence: 99%
“…Anera et al 18 found that the SR diminished 3 months after LASIK. Ondategui et al 17 found that MTF cutoff and SR decreased and OSI increased 3 months after photorefractive keratectomy (PRK) and LASIK surgery. It is reported that higher degrees of myopia have an adverse effect on quality of life.…”
mentioning
confidence: 99%
“…Wavefront analysis has been widely used to isolate the effects of lower order aberrations and higher order aberrations, and to evaluate the contributions of individual aberrations on optical quality 13. With the development of new techniques and devices such as the double-pass system, optical quality can also be measured more precisely 8,14,15,16. The Optical Quality Analysis System (Visiometrics, Terrassa, Spain), a commercially available double-pass device, has been introduced to measure optical quality associated parameters objectively and accurately in clinical practice 17.…”
Section: Introductionmentioning
confidence: 99%